Isotemporal substitution of sedentary time with physical activity and sleeping time: associations with body composition among individuals with prediabetes - M. Torres-Carballo; M. Torres-Carballo; A. M. Galmes-Panades; A. M. Galmes-Panades; A. M. Galmes-Panades; M. Arias-Fernández; M. Arias-Fernández; M. Arias-Fernández; A. Huguet-Torres; A. Huguet-Torres; M. Abbate; M. Abbate; et al. (Frontiers in Sports and Active Living)
AimTo assess the association between physical activity (PA), sedentary time (ST), and sleep with body composition, and to explore the effects of reallocating ST to PA or sleep on body composition in individuals with prediabetes and overweight/obesity.Material, methods and resultsBaseline data from the PREDIPHONE trial, including 159 participants (mean age 59.6 years) with prediabetes (Fasting Plasma Glucose 100–125 mg/dl) and overweight/obesity (Body Mass Index 27–40 kg/m²), were analyzed. Body composition was assessed via bioelectrical impedance, while PA, ST, and sleep were measured with accelerometry. Linear regression and isotemporal substitution models evaluated associations. Increased ST was positively associated with body fat mass (kg) (β = 0.016; CI 95%: 0.003–0.030), body fat mass (%) (β = 0.009; 0.001–0.018), and visceral adipose tissue (β = 0.005; 0.001–0.010). Moderate-to-vigorous PA (MVPA) was negatively associated with body fat mass (kg) [β = −0.031; 0.055- (−0.008)], body fat mass (%) [β = −0.017; −0.032-(−0.003)], and Visceral adipose tissue [β = −0.009; −0.02-(−0.002)]. Replacing ST with MVPA was linked to lower Visceral adipose tissue [β = −0.012; −0.024-(−0.001)] and body fat mass (kg) [β = −0.039; −0.074-(−0.006)], but not with lean mass. No significant associations were found when substituting ST with light PA or sleep.DiscussionIn individuals with prediabetes and overweight/obesity, replacing ST with MVPA could reduce body fat and VAT but not increases lean mass.